Laboratory Diagnosis of Dengue: A Review - DS, Shamala (IIUM Medical Journal Malaysia, 2015)
Dengue is an arthropod borne disease that has become important worldwide. There is still no specific drug available for treatment and also no protective vaccine that can be used. As such, specific diagnosis is essential to enable good management and prevention of large outbreaks. Diagnosis today in many countries is still based on serology though the detection of NS1 has slowly become incorporated. Diagnosis is critical for early intervention with specific preventive health measures to prevent fatalities and also to curtail spread and reduce economic losses. Serological assays mainly detect IgM which now as a single test is invalid unless a second sample is taken to confirm. As such to effectively diagnose dengue at all stages of infection, assays with two or more markers are required or two samples taken a few days apart. Other commonly used tests include NS1 detection, nucleic acid amplification and IgG detection. However the sensitivities of the current commercial kits vary quite considerably and have to be interpreted with caution. Hence knowledge of this disease is essential when conducting diagnostics for dengue.